2017
DOI: 10.1515/frp-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

New location of the moss Buxbaumia viridis in the Białowieża Forest

Abstract: This paper describes a new occurrence and location of the green shield moss Buxbaumia viridis (Moug. ex Lam. & DC.) Brid. ex Moug. & Nestl. in the Białowieża Forest. One sporophyte was found on a decaying spruce log. However, its existence and the present environmental conditions of the site are threatened by the death of spruce trees. The dying of the spruce trees is expected for the near future and will lead to altered shade conditions impacting on the shield moss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
1
3
0
Order By: Relevance
“…B. viridis was more often found in areas with a recent history of management practices than in areas that had not undergone treatment for at least 15 years (or ever), with the difference being statistically significant. This is consistent with the findings of Holá et al [23], Gawryś and Szulc [49], and Deme et al [40] and contradicts the view that only protected areas (nature reserves and national parks such as the BNP) provide suitable habitats for the studied moss species [25] and that strict legal protection is the best way of maintaining B. viridis localities [1]. Thus, calls for creating protective zones around B. viridis localities in managed forests are unsubstantiated [1,10,19,20,31,34,50].…”
Section: Discussionsupporting
confidence: 93%
“…B. viridis was more often found in areas with a recent history of management practices than in areas that had not undergone treatment for at least 15 years (or ever), with the difference being statistically significant. This is consistent with the findings of Holá et al [23], Gawryś and Szulc [49], and Deme et al [40] and contradicts the view that only protected areas (nature reserves and national parks such as the BNP) provide suitable habitats for the studied moss species [25] and that strict legal protection is the best way of maintaining B. viridis localities [1]. Thus, calls for creating protective zones around B. viridis localities in managed forests are unsubstantiated [1,10,19,20,31,34,50].…”
Section: Discussionsupporting
confidence: 93%
“…viridis is often associated with old-growth forests as they tend to be more humid, and to contain larger amounts of coarse wood debris [36]. However, over recent years, increasing doubts have been raised about the status of B. viridis as a characteristic species of ancient or natural forests [5,9]. Published studies and our own observations have demonstrated the occurrence of the species in strongly managed forests [5,9], often in young Douglas-fir or spruce plantations.…”
Section: Conservation Implicationsmentioning
confidence: 95%
“…We assume that the species occurs frequently as protonema only, and that a slight opening of the canopy could be one of the factors initiating the development of sporophytes. Observations of sporophytes in B. viridis are mostly sporadic and scarce [9,30,31], and they could be explained by the generally suboptimal availability of light at forest scale. Our results need to be further investigated as the microtopography of the microhabitat could affect light availability, and thus response to canopy opening [32].…”
Section: Habitat and Microhabitat Comparison Between Protonemal And Smentioning
confidence: 99%
See 1 more Smart Citation